Black, Jewish, and interracial : it's not the color of your skin, but the race of your kin, and other myths of identity - Azoulay, Katya Gibel (E-Duke books scholarly collection., 1997)
A study on being Black and Jewish in the United States. Author discusses bi-racialism and how and why African-Americans of Jewish descent identify themselves with other groups who have had a history of legal, political and racial discrimination.